Evolution of the World Wide Fund for Nature as a Hegemonic Actor in Global Conservation Governance and Its Impact on the Baka Community - Zamharirah Sang Putri; Bright Malenga (Universitas Tribhuwana Tungga Dewi, 2026)
This study examines the evolution of the World Wide Fund for Nature (WWF) and its influence on global environmental governance, focusing on the case of the Baka Indigenous people in Cameroon. The study aims to analyze how WWF’s transformation from a wildlife conservation organization into a transnational actor has shaped power relations among international institutions, states, corporations, and Indigenous communities. This research applies Decolonial Theory, the concept of green grabbing, and the perspectives of Boaventura de Sousa Santos and Elinor Ostrom to critically examine conservation practices. The findings show that WWF has played a significant role in environmental advocacy, conservation funding, knowledge production, and protected area governance. However, the Baka case reveals that global conservation can reproduce coloniality of power when implemented without meaningful Indigenous participation. Restricted forest access, the use of eco-guards, and weak accountability for alleged human rights abuses reflect a tension between ecological protection and collective community rights. This study concludes that just conservation must be participatory, dialogical, rights-based, and grounded in the recognition of local knowledge as a core foundation of global environmental governance.